2021
DOI: 10.35445/alishlah.v13i1.479
|View full text |Cite
|
Sign up to set email alerts
|

Video Project Model for Increasing English Speaking Skills in Covid-19 Pandemic

Abstract: The purpose of the study was to know the increase of English speaking using video project.  Moreover, the covid-19 pandemic era needs a learning process that can give appropriate facility for online learning. The method of study used one-group experimental. The participant was 25 students that are taken randomly. Data analysis used paired sample t-test. The results showed that there was an increase in the ability to speak English. From each component of the ability to speak English, the average score also incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The results of the observation indicate that using a video project in teaching speaking improves the students' speaking ability. Thus, the results of this study confirmed the results of the previous studies concerning the positive effect of using video projects in teaching speaking [13][14][15][16][17].…”
Section: Benefits Of Using a Video Project To Students' Speaking Abilitysupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the observation indicate that using a video project in teaching speaking improves the students' speaking ability. Thus, the results of this study confirmed the results of the previous studies concerning the positive effect of using video projects in teaching speaking [13][14][15][16][17].…”
Section: Benefits Of Using a Video Project To Students' Speaking Abilitysupporting
confidence: 90%
“…Nowadays, students are used to making videos containing their daily routines, hobbies, and other preferences; therefore, they might not find any difficulties in making a video project. Studies on using video projects in teaching speaking to EFL learners have been conducted by previous researchers [13][14][15][16][17]. Khawa [16] found that using a video-making project is significantly effective in improving the students' speaking ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So the class was more like students centered learning and task based learning. Video project model for increasing English speaking skills in covid-19 pandemic was applied in this case (Baron, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Students and teachers must be prepared to utilize the video project to foster an interest in learning (Baron, 2021). Thus, the study must be conducted to ascertain students' inventiveness to complete the project and improve their speaking abilities.…”
Section: Introductionmentioning
confidence: 99%